2018
DOI: 10.1021/jacs.7b09453
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Diffusion Anisotropy of Carbon Dioxide in the Metal–Organic Framework Zn2(dobpdc)

Abstract: Metal-organic frameworks are promising materials for energy-efficient gas separations, but little is known about the diffusion of adsorbates in materials featuring one-dimensional porosity at the nanoscale. An understanding of the interplay between framework structure and gas diffusion is crucial for the practical application of these materials as adsorbents or in mixed-matrix membranes, since the rate of gas diffusion within the adsorbent pores impacts the required size (and therefore cost) of the adsorbent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 78 publications
8
105
3
Order By: Relevance
“…18,48−56 By analyzing the line shape changes as a function of the applied pulsed field gradient, we obtained values for the self-diffusion parallel (D ∥ ) and perpendicular (D ⊥ ) to the MOF channels. 22 The obtained nonzero value of D ⊥ was unexpected given the onedimensional channels in the crystal structure obtained by single-crystal X-ray diffraction, and we suggested that structural defects are responsible. In our previous work we noted, "The dominant source of error in our analysis is most likely systematic error arising from the finite peak line widths that arise from homogeneous broadening, such that for a given δ, crystals at a range of θ values contribute to the signal," 22 where θ is the angle between the crystallographic c-axis and the applied magnetic field, B 0 .…”
Section: ■ Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…18,48−56 By analyzing the line shape changes as a function of the applied pulsed field gradient, we obtained values for the self-diffusion parallel (D ∥ ) and perpendicular (D ⊥ ) to the MOF channels. 22 The obtained nonzero value of D ⊥ was unexpected given the onedimensional channels in the crystal structure obtained by single-crystal X-ray diffraction, and we suggested that structural defects are responsible. In our previous work we noted, "The dominant source of error in our analysis is most likely systematic error arising from the finite peak line widths that arise from homogeneous broadening, such that for a given δ, crystals at a range of θ values contribute to the signal," 22 where θ is the angle between the crystallographic c-axis and the applied magnetic field, B 0 .…”
Section: ■ Introductionmentioning
confidence: 79%
“…We recently used this latter approach to study the anisotropic diffusion of CO 2 in the MOF Zn 2 (dobpdc) ( Figure 1) (dobpdc 4− = 4,4′-dioxidobiphenyl-3,3′-dicarboxylate), 22 a material from a wider MOF family that has shown promise for CO 2 capture from power station flue gases. 2,38−47 The residual chemical shift anisotropy for pore-confined CO 2 rendered the chemical shift dependent on crystal orientation, 22 as in several other NMR studies of CO 2 in MOFs. 18,48−56 By analyzing the line shape changes as a function of the applied pulsed field gradient, we obtained values for the self-diffusion parallel (D ∥ ) and perpendicular (D ⊥ ) to the MOF channels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Long‐ and short‐range CO 2 dynamics can both be studied using SSNMR spectroscopy. Even though long‐range studies can provide important information on diffusivity, local CO 2 dynamics has been the main focus for many of the recent SSNMR investigations. Hence, we restrict our current discussion to local CO 2 dynamics studies.…”
Section: Carbon Dioxide (Co2)mentioning
confidence: 99%
“…MOFs are promising CO 2 adsorbents, [13] and SSNMR spectroscopy has been employed to studyC O 2 chemisorptiona nd physisorption in severalM OFs. [12] This section focuses on physisorptiona nd demonstrates how guest dynamics, [14][15][16][17][18][19][20][21][22] MOF-CO 2 interaction strengths [16] and binding sites [16,17] can be investigated.…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 99%
See 1 more Smart Citation